Retrograde transradial Approach for Hemodialysis Access Intervention: A Single-Center Study - Hossain, GM Mokbul; Mandal, Naresh Chandra; Hasan, Rakibul; Dey, Nirmal Kanti; Mamun, Abdullah Al; Saklayen, SMG; Sarker, Swadesh Ranjan; Sarker, Motiur Rahman; Huque, AKM Ziaul; Ferdous, Shajadi; et al. (Bangladesh Heart Journal, 2020)
Perianastomotic stenosis is a common scenario after creation of arteriovenous fistula for hemodialysis. Most of the interventionists prefer transvenous approach. But transradial approach can easily visualize radial artery and cephalic venous tree up to central vein. This retrospective study was performed from November 2012 to January 2017 in Ibn Sina Hospital, Dhanmondi, Dhaka. Total patients undergoing hemodialysis access were 148 (male 74, female 74, male-female ratio 1:1). Number of radiocephalic fistula was 95 (64%), brachiocephalic fistula 50 (34%) & others 3 (2%). Most of the punctures were done by palpation. Sometimes puncture was made by ultrasonogram guidance. Puncture needle size was 21 gauge, 2.5cm or 4cm long. Sheath size was 6 F x 4 cm or 7 F x 4cm. Majority of the cases (140) were successfully approached through retrograde transradial route. Few cases (8) were approached through retrograde venous route due to thrombosis of radial artery for previous intervention or creation of radiocephalic fistula in an end to end fashion. It was concluded that retrograde transradial approach to dilate perianastomotic stenosis as well as outflow vein is a good option. Bangladesh Heart Journal 2020; 35(1) : 54-60